Design and Fast Prototyping of a Wearable Safety Device for Divers. Issue 21 (2016) - Allotta, Benedetto; Pugi, Luca; Gelli, Jonathan; Lupia, Marco
Abstract: Object of this work is the design and the development of the prototype of an innovative wearable mechatronics device able to increase the safety of divers. In particular the proposed system briefly called SARIS is a patented electronic device pluggable on standard over pressure valves of scuba jackets aimed at detecting the occurrence of too fast, possibly uncontrolled, ascents of the diver. In that case, it opens automatically the jacket's overpressure valves for reducing its volume and stopping the ascent. In particular authors starting from the original specifications of Applicon SRL, the owner of the patent and customer of the application, developed original design criteria and successfully tested a working prototype of the device. In this work the design process of the innovative system are deeply explained and commented